2022
DOI: 10.1177/13623613221102736
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all for parent-mediated autism interventions: A randomized clinical trial

Abstract: Coaching parents to use language facilitation strategies improves long-term language outcomes for autistic children. To optimize parent-mediated interventions, more studies need to explore factors that influence parents’ learning. This study involved 119 autistic children (18–48 months) and their biological mothers enrolled in a single-site, factorial randomized clinical trial. Mothers were taught to use one of two types of language facilitation strategies (responsive or directive) during eight weekly, hour-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Results of the current study demonstrated that children in the directive group obtained better language outcomes than children in the responsive group. However, findings of Roberts et al (2022) demonstrated that caregivers in the responsive group used strategies more frequently and accurately than caregivers in the directive group, regardless of their learning style (as indicated by BAP status). Taken together, a critical next step to characterizing the mechanisms of caregiver-mediated NDBIs is understanding the extent to which caregiver fidelity (i.e.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Results of the current study demonstrated that children in the directive group obtained better language outcomes than children in the responsive group. However, findings of Roberts et al (2022) demonstrated that caregivers in the responsive group used strategies more frequently and accurately than caregivers in the directive group, regardless of their learning style (as indicated by BAP status). Taken together, a critical next step to characterizing the mechanisms of caregiver-mediated NDBIs is understanding the extent to which caregiver fidelity (i.e.…”
Section: Discussionmentioning
confidence: 85%
“…The randomization sequence was computer generated by the senior project statistician and contained random block sizes with a 1:1 assignment ratio within blocks. Based on the primary aims of the clinical (Roberts et al, 2022), randomization was stratified on child verbal status and maternal BAP status (i.e. presence or absence of subclinical characteristics of autism).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 This variability underlines the need for tailored interventions and support structures, moving away from the idea that one-size-fits-all solutions, as often promoted in evidence-based research, are sufficient. 55 - 58 Various social factors and medical comorbidities among our studied population showed different impacts on social participation, which needs to be considered when developing interventions and support structures.…”
Section: Discussionmentioning
confidence: 98%
“…Roberts et al. ( 2022 ) provides further information about intervention strategies. This study contained three time points: participants were assessed and completed questionnaires before intervention (i.e., T0), immediately after intervention (i.e., T1), and at 3 months post‐intervention follow‐up (i.e., T2).…”
Section: Methodsmentioning
confidence: 99%